2014
DOI: 10.5194/bgd-11-7273-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of extracellular polymeric substances (EPS) from <i>Pseudomonas putida</i> strain MnB1 in dissolution of natural rhodochrosite

Abstract: <p><strong>Abstract.</strong> Microbially mediated oxidation of Mn(II) to Mn oxides have been demonstrated in previous studies, however, the mechanisms of bacteria how to dissolve and oxidize using a solid Mn(II) origin are poorly understood. In this study, we examined the role of extracellular polymeric substances (EPS) from <i>P. putida</i> strain MnB1 in enhancing dissolution of natural rhodochrosite. The results showed that <i>P. putida</i> strain MnB1 cell can eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Therefore, these FT-IR results in MCP-4 to MCP-9 suggest that the functional groups of N–H in amine (protein), C O in amide I, and C–O in urethane (carbamic acid) could be due to the formation of BISMCP; it is comparable with the previous results of Enyedi et al [ 26 ]. Since all samples (MCP-4 to MCP-9) contained the CO 3 2− band and FT-IR bands matched to the previous study [ 3 , 26 , 87 , 79 ]; the functional groups in this study can be likewise identified as rhodochrosite mineral or MnCO 3 material [ 3 , 26 , 79 , 86 ].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, these FT-IR results in MCP-4 to MCP-9 suggest that the functional groups of N–H in amine (protein), C O in amide I, and C–O in urethane (carbamic acid) could be due to the formation of BISMCP; it is comparable with the previous results of Enyedi et al [ 26 ]. Since all samples (MCP-4 to MCP-9) contained the CO 3 2− band and FT-IR bands matched to the previous study [ 3 , 26 , 87 , 79 ]; the functional groups in this study can be likewise identified as rhodochrosite mineral or MnCO 3 material [ 3 , 26 , 79 , 86 ].…”
Section: Resultssupporting
confidence: 74%
“…The absorption bands at 1641.79 cm −1 in all samples MCP-4 to MCP-9 indeed confirm the existence of C O binding and strong stretching of CO 3 2− in Amide I [ [3] , [80] ]. Moreover, the weak adsorption band at 1081.34 cm −1 is related to symmetric C–O stretching in the urethane group [ 3 , 37 , 61 , 79 , 83 ]. In addition, the bands at 805.22 cm −1 are occupied by the phosphate group of the P–CH 3 binding and the strong stretching silicon group of the Si–O binding.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas putida strain MnB1 EPS can enhance the dissolution of rhodochrosite in mediums with pH ranging from 5.0 to 8.0. This effect can be attributed to N-H, C=O and C-H groups found in EPS (Wang and Pan 2014).…”
Section: Resultsmentioning
confidence: 94%